2017
DOI: 10.1007/s00381-017-3442-x
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal management of fetal neurosurgical diseases

Abstract: The advance in the imaging tools during the pregnancy (ultrasound and magnetic resonance) allowed the early diagnose of many fetal diseases, including the neurological conditions. This progress brought the neurosurgeons the possibility to propose treatments even before birth. Myelomeningocele is the most recognized disease that can be treated during pregnancy with a high rate of success. Additionally, this field can be extended to other conditions such as hydrocephalus and encephaloceles. However, each one of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 54 publications
1
49
0
Order By: Relevance
“…In all cases, the skin could be closed, and the healing process was effective without the use of exogenous material. 15 …”
Section: Methodsmentioning
confidence: 99%
“…In all cases, the skin could be closed, and the healing process was effective without the use of exogenous material. 15 …”
Section: Methodsmentioning
confidence: 99%
“…Large amounts of neuronal tissue inside the defect are generally associated with microcephaly. Hydrocephalus and microcephalus are the most critical risk factors . It has been reported that the encephalocele defects located on the occipital region have a worse prognosis than those developed in the frontal region .…”
Section: Discussionmentioning
confidence: 99%
“…Encephalocele is a cranial bone defect, which is characterized by protrusion of the meninges and/or neural tissue through the defect . This sac‐like protrusion is covered by skin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This protocol follows the same recommendations with regard to the criteria for screening patients, preoperative evaluation protocol, and postoperative care, with an exception for the opening and closure of the uterus due to the legal impediment in our country which precludes the use of a uterine stapler without being licensed by a governmental agency. This impediment forced us to develop an alternative surgical technique …”
Section: Introductionmentioning
confidence: 99%